State and Trends of Carbon Pricing 2019 - World Bank Group (Washington, DC: World Bank, 2019)
This report provides an up-to-date overview of existing and emerging carbon pricing instruments around the world, including international, national and subnational initiatives. It also investigates trends surrounding the development and implementation of carbon pricing instruments and how they could accelerate the delivery of long-term mitigation goals. This edition also discusses the relation between policies that put an explicit price on carbon and policies that put an implicit price on carbon.